Soil phosphorus availability with irrigation and nitrogen in pearl millet-mustard cropping system - SINGH, R. K.; SRIVASTAVA, AJAYA; SINGH, VEER (Journal of Soil and Water Conservation, 2020)
A field study was conducted during 2005-06, 2006-07 and 2007-08 to evaluate out the effect of continuous use of N fertilizer and irrigation on soil available P at different soil depth under pearl millet-mustard based cropping system in a semi-arid environment. Available soil P increased with increasing levels of nitrogen in all soil depths. It was highest in surface layers (0-15 cm) and decreased with increasing depths. The availability of soil P was slightly higher in irrigated plots than in unirrigated with all N levels. Available soil P was highest 23.0 kg ha-1 under irrigated condition with 120 kg N kg ha-1 at harvest stage. In case of mustard varieties, soil P in general increased in surface layer as the dates of sowing advanced and decreased with the depth. At the harvest time of mustard, the available soil P increased marginally with increase in irrigation and N levels at all soil depths except at 15-30 cm for N level. However, the maximum increase in available soil P of 1.48 and 1.04 kg ha-1 was observed at surface than other depths owing to irrigation and N levels, respectively.